Evaluation of acoustic shielding effects from a generic GARTEUR helicopter configuration - Yin, J.; Rossignol, K.S.; Reboul, G.; Mortain, F.; Vigevano, L.; Zanotti, A.; Gibertini, G.; Barbarino, M.; Testa, C.; Bernardini, G.; Brouwer, H. (My University, 2021)
This paper presents the activities in the GARTEUR Action Group HC/AG-24 to study the noise scattering of helicopter rotors in the presence of the fuselage. The focus of the Action Group is on the development and the validation of numerical prediction methods and on establishing an experimental data base for numerical validations. This paper will focus on the results from the wind tunnel and the numerical activities achieved in the last stage of the project. Shielding experiments were conducted in DLR’s Acoustic Wind tunnel in Braunschweig (AWB) using point and rotor noise sources. The numerical methods used in the group include Boundary Element Method (BEM) for solving the Helmholtz equation and Computational AeroAcoustic method (CAA) for solving the linearized Euler equations. The acoustic scattering predictions are compared to test data.